Scheme of Derived Moduli Problem to the “quantum” version of an algebra symT. - Prof. Dr. Francisco Bulnes; Prof. Dr. Ivan Verkelov (IJRDO -JOURNAL OF MATHEMATICS, 2020)
In this research, will be obtained the 8 -category analogous more algebraic structures like commutative rings to obtain the “quantum” version of an algebra symT, through consider a scheme to a moduli problem on afield k (class field) of all equivalences that are satisfied in the context of them moduli schemes and “CRings”. Also is given a short classification of derived moduli problems and their elements in moduli stacks